Profits in the modern economy ... selected papers from a conference on Understanding Profits - Stevenson, Harold W.; Nelson, J. Russell; Macalester College; University of Minnesota (Minneapolis : University of Minnesota Press, 1967)
This volume provides the serious reader with a comprehensive discussion of the current beliefs about the role of profits in an economy.
Includes bibliographical footnotes and index.
hza 01/07/2018
Loans
Keywords: Profit; Profit